A shared socio-economic pathway based framework for characterising future emissions of chemicals to the natural environment. (December 2022) - Desrousseaux, Alizée; Nagesh, Poornima; Gajraj, Rudrani; Dekker, Stefan; Eitzinger, Josef; Sallach, Jonathan B.; Boxall, Alistair; Kok, Kasper
Abstract: Chemicals are used in all aspects of our lives and are either intentionally or unintentionally released into the natural environment, leading to chemical pollution which negatively effects biodiversity and ecosystem and human health. The world is going through socio-economic, climate and technological changes that will affect chemical emissions to the natural environment but the extent of these affects is unknown. Scenarios of future chemical emissions are therefore needed to inform research and policy decisions to protect the health of humans and ecosystems into the future. In this article, we present a framework, based on Shared Socio-economics Pathways (SSPs) in combination with Representative concentration pathways (RCPs), to develop future chemical environmental emissions scenarios for single molecules or groups of chemicals sharing similar features. The framework has 4 steps: 1) determination of the characteristics of the scenario; 2) review and prioritisation of socio-economics and climate drivers; 3) development of scenarios; and 4) consistency checks. The framework is demonstrated for antidepressant and insecticide emissions into European freshwater-systems in 2050. Output narratives provide multiple pathways of chemical emissions in the future and can be used by researchers, regulators, politicians, governments, and the private sector to develop mitigation and adaptation strategies to chemical pollution issue. Highlights: We develop a framework to extend SSPs to any molecules or group of chemicals sharing similar features. Antidepressants and insecticides emissions scenarios are developed for European freshwater systems in 2050. This framework illustrates the first storyline looking at chemical emissions in the future under the SSPs storylines.